2013
DOI: 10.1111/cas.12234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiation on the incidence of prostate cancer among Nagasaki atomic bomb survivors

Abstract: Atomic bomb survivors have been reported to have an increased risk of some cancers, especially leukemia. However, the risk of prostate cancer in atomic bomb survivors is not known to have been examined previously. This study examined the association between atomic bomb radiation and the incidence of prostate cancer among male Nagasaki atomic bomb survivors. The subjects were classified by distance from the hypocenter into a proximal group (<2 km), a distal group (≥2 km), and an early entrance group (those who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Prostate cancer has a large genetic risk factor; risk factors shared with other cancers have not yet been identified . In addition, smoking, which is an important risk factor for many cancers, is reportedly associated with a decreased risk of prostate cancer . We have to also consider socioeconomic status (SES) such as educational attainment and income, which is correlated with cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer has a large genetic risk factor; risk factors shared with other cancers have not yet been identified . In addition, smoking, which is an important risk factor for many cancers, is reportedly associated with a decreased risk of prostate cancer . We have to also consider socioeconomic status (SES) such as educational attainment and income, which is correlated with cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Because prostate cancer is generally less fatal than most major cancers, incidence rates are a better measure of risk than mortality rates, but the dormant nature of prostate cancer makes incidence studies more prone to screening bias. To our knowledge, a study by Kondo et al ( 10 ) of the Nagasaki atomic bomb survivors has been the only other radiation study that considered the possible effect of PSA tests in that the analysis excluded prostate cancer cases diagnosed by screening. That study found an increased incidence risk of prostate cancer for proximally compared with distally exposed survivors.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies of nuclear workers have estimated the radiation-related excess relative risk (ERR) per Gy that ranged from below zero (–1.18) to 0.19 in studies of prostate cancer mortality and from below zero (–0.34) to 0.16 in studies of prostate cancer incidence, with none of these estimates being significantly different from zero ( 49 ) (; https://doi.org/10.1667/RADE-22-00089.1.S1). Kondo et al ( 10 ) have reported an increased risk of prostate cancer incidence among proximally exposed atomic bomb survivors in Nagasaki followed through 2009, but no dose response analysis was performed. Studies of cancer incidence and mortality data in the Life Span Study (LSS) cohort of Japanese atomic bomb survivors from Hiroshima and Nagasaki, with shorter follow-up, consistently suggested a modestly elevated risk of prostate cancer associated with radiation but without reaching the level of statistical significance ( 11, 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also observed an increased risk of prostate cancer (SIR = 1.92), one of the few solid cancers not associated with radiation exposure in most studies. 24,37,38 Nevertheless, in a recent study, Kondo et al 39 have shown a significant association between atomic bomb radiation and prostate cancer, stating their study was the first report revealing this association. Still, this remains a controversial issue, and we cannot exclude a possible relation to non-radiation causes, as previously hypothesised for stomach and lung cancer.…”
Section: Antunes Et Almentioning
confidence: 98%